PtoMYB031, the R2R3 MYB transcription factor involved in secondary cell wall biosynthesis in poplar - Tang, Feng; Jiao, Bo; Zhang, Meng; He, Minghui; Su, Ruiying; Luo, Keming; Lan, Ting (Frontiers in Plant Science, 2024)
Introduction The biosynthesis of the secondary cell wall (SCW) is orchestrated by an intricate hierarchical transcriptional regulatory network. This network is initiated by first-layer master switches, SCW-NAC transcription factors, which in turn activate the second-layer master switches MYBs. These switches play a crucial role in regulating xylem specification and differentiation during SCW formation. However, the roles of most MYBs in woody plants are yet to be fully understood. Methods In this study, we identified and isolated the R2R3-MYB transcription factor, PtoMYB031, from Populus tomentosa. We explored its expression, mainly in xylem tissues, and its role as a transcriptional repressor in the nucleus. We used overexpression and RNA interference techniques in poplar, along with Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays, to analyze the regulatory effects of PtoMYB031. Results Overexpression of PtoMYB031 in poplar significantly reduced lignin, cellulose, and hemicellulose content, and inhibited vascular development in stems, resulting in decreased SCW thickness in xylem tissues. Gene expression analysis showed that structural genes involved in SCW biosynthesis were downregulated in PtoMYB031-OE lines. Conversely, RNA interference of PtoMYB031 increased these compounds. Additionally, PtoMYB031 was found to recruit the repressor PtoZAT11, forming a transcriptional inhibition complex. Discussion Our findings provide new insights into how PtoMYB031, through its interaction with PtoZAT11, forms a complex that can suppress the expression of key regulatory genes, PtoWND1A and PtoWND2B, in SCW biosynthesis. This study enhances our understanding of the transcriptional regulation involved in SCW formation in poplar, highlighting the significant role of PtoMYB031.